The Role of Organizational Communication in Quality Assurance in Higher Education Institutions According to Joseph Goran’s Quality Model (A field study on Sudan University of Science and Technology - Khartoum City- Sudan) - Osman, Anjom Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identify the level of organizational communication according to the fields of (effectiveness of formal communication - communication skills of superiors) and its impact on quality assurance according to the model of Joseph Goran model of quality (quality planning - quality control - continuous improvement of quality) at Sudan University of Science and Technology - Khartoum City - the descriptive analytical methodology was utilized to reach the result, the study population consists of (600) faculty members depending on the varibles of (degree - specialization - years of experience),So the researcher designed a questionnaire as a tool for collecting information and applied it to the sample of the study of (236) members, After the processing of the data, a number of results were reached, the most important of which were:Organizational communication fields are practiced in medium degree with an arithmetic mean (3.14), and the practice of quality assurance operations according to the model of (Joseph Goran) is done with a weak degree with an arithmetic average (2.60), and existence of a positive direct relationship between the dimensions of effective organizational communication (effectiveness of formal communication - communication skills of superiors) and quality assurance processes according to the model of Joseph Goran (quality planning - quality control - continuous improvement), and recommended a number of recommendations, the most important of which were: the development of an effective organizational communication system that allows the participation of university employees in decision-making processes, ensures the flow of information, guidance and adequate organizational support and promotes transparency.